2018
DOI: 10.31326/jcpaud.v1i02.190
|View full text |Cite
|
Sign up to set email alerts
|

Membangun Pengetahuan Anak Usia Dini Melalui Permainan Konstruktif Berdasarkan Perspektif Teori Piaget

Abstract: Knowledge is important in the child development process because knowledge is the basis of  attitudes and self skills formation . Familiarizing children to build their own knowledge  early  can make them capable for finding ideas to solve problems, having good self-confidence  and initiative. Children are active beings who can build their own knowledge through play. When playing, child exploring, finding and utilizing the objects around them  to be meaningful. Exploring objects enable the assimilation and accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
5
0
5
Order By: Relevance
“…This view is contrary to structuralism and positivism that socio-cultural is a reality. Constructivism is a flow of Epistemological Philosophy that assumes that knowledge results from construction or human formation (Candy, 1989 Constructivism assumes that humans can construct or build knowledge after interacting with their environment (Amineh & Asl, 2015; Ginting, 2018). Constructivism is concerned with how individuals learn, not how teachers teach (Suparlan, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This view is contrary to structuralism and positivism that socio-cultural is a reality. Constructivism is a flow of Epistemological Philosophy that assumes that knowledge results from construction or human formation (Candy, 1989 Constructivism assumes that humans can construct or build knowledge after interacting with their environment (Amineh & Asl, 2015; Ginting, 2018). Constructivism is concerned with how individuals learn, not how teachers teach (Suparlan, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The ninth study in 2018 was an experimental research conducted by Meta Br Ginting entitled Building Early Childhood Knowledge Through Constructive Games Based On The Perspective Of Theory Of Piaget. The results of this study found that by playing constructively children gain knowledge through the process of assimilation and accommodation so as to help children form new schemes based on the experience gained and produce knowledge (Ginting, 2018).…”
Section: A Introductionmentioning
confidence: 84%
“…Menurut Piaget terdapat fungsi penting bermain (Ginting, 2018) adalah memberi anakanak kesempatan supaya membiasakan terhadap kenyataan. Terciptanya lingkungan belajar memungkinkan anak belajar sambil bermain dan bermain sambil belajar secara efisien merupakan konsekuensi dari berbagai pemikiran tentang nilai bermain untuk pembelajaran di Taman Kanak-Kanak.…”
Section: Pembahasanunclassified